Haiti : Enhanced Initiative for Heavily Indebted Poor Countries; Decision Point Document. (IMF Staff Country Reports; Country Report, 2006)
This paper presents an assessment of Haiti's qualification for assistance under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. Poverty Reduction and Growth Facility (PRGF) arrangement is scheduled to be discussed by the IMF Executive Board in parallel with this document. The impact of prolonged political conflicts and violence, periods of high external assistance followed by the withdrawal of economic support, and natural disasters has been severe. The government has begun the preparation of a full Poverty Reduction Strategy Paper (PRSP). An important objective of the authorities is to achieve robust and sustainable real economic growth.